A Case Report of Rehabilitation of Nitrous Oxide Intoxication - Yiming XU; Honghua SHEN; Qin ZHANG; Lei REN (康复学报)
Objective:To observe the clinical effect of rehabilitation therapy on nitrous oxide intoxication.Methods:A case of a patient with nitrous oxide intoxication was collected, and multifarious rehabilitation therapies were used. Initially, exercise therapy was used to increase the patient's myodynamia, 60 minutes a day, six days a week. Furthermore, individualization occupational therapy was designed according to the patient's condition to promote his activity of daily living, 30 minutes a day, six days a week. Additionally, speech therapy was used to improve his reading comprehension ability, 30 minutes a day, seven days a week. Other physical agent therapy and local irradiation were used to improve circulation and promote neural restoration, 60 minutes a day, six days a week. Finally, psychological therapy was accepted for two month, once a month. The motor function, cognition function, speech and swallowing function, activity of daily living and mentality of the patient were assessed before and after treatment.Results:After two months rehabilitation therapy, the patient could take care of himself except shower and climing stairs. Prime target achieved completely.Conclusion:Patients with nitrous oxide intoxication in stable condition should received rehabilitation therapy as soon as possible and throughout the treatment if rehabilitation measure is available.